Experiential Marketing Terhadap Kepuasan Konsumen Pada Fitur NR Aplikasi Bibit - Retnoningtyas Dwi Handayani; Elly Mirati (POLITEKNIK LP3I JAKARTA, 2023)
Technological changes that are developing rapidly have led to high competition between investment startups and securities. Therefore, investment startup companies need to implement marketing strategies that are appropriate and right on target in order to win in market competition. One of the marketing strategies used by investment startup companies is experiential marketing. This marketing strategy focuses on providing a positive experience in the mind of customers so that consumer satisfaction is achieved. Experiential marketing strategies can be implemented into a creative and innovative feature. Total of 100 respondents have been obtained and met the research criteria, namely users of the Bibit application and the routine saving feature. The data analysis technique used in this study is Multiple Linear Regression Analysis using SPSS version 25. The results of this study are that the feel, think, and relate factors have a significant effects on customer satisfaction. Meanwhile, sense and act factors have no significant effects on consumer satisfaction. Sense, feel, think, act, and relate factors simultaneously have a significant effects on customer satisfaction.Key words: Investment StartUp, Experiential Marketing, and Customer Satisfaction